Optimization ofhybrid flow shop scheduling in a machine shop: Achieving energy efficiency and minimizing machine idleness with multi-objective Tiki Taka optimization - Siti Nurhazwani Husna, Mohd Hata; Muhammad Ammar, Nik Mu’tasim; Mohd Fadzil Faisae, Ab Rashid (Faculty Mechanical Engineering, UMP, 2025)
Hybrid flow shop scheduling (HFS) has garnered significant interest in terms of problem formulation and solution approaches. This work introduces an optimization approach for a case study on a hybrid flow shop scheduling problem. The objective is to minimize the makespan, energy consumption, and idle machines in the manufacturing shop. The HFS comprises multipleconcurrent production lines, each composed ofseveral machinesthat operatein one or more stages. A case study was conducted using fourteen jobs across three stages, which involved the use oflathes, millingmachines, and deburring machines. The EE-HFS was optimized using Multi-Objective Tiki Taka Optimization (MOTTA).The study considered machine idle time as a key factor influencing energy efficiency, incorporating it into the scheduling evaluation.The optimization result was compared to established algorithms, such as the Non-dominated Sorting Genetic Algorithm-II, the Multi-ObjectiveEvolutionary Algorithm Based on Decomposition, the Multi-ObjectiveParticle Swarm Optimization,and the recent algorithm,the Multi-ObjectiveGrey Wolf Optimizer. The metrics used for comparison include Error Ratio (ER), Pareto Percentage (%), Spacing, Maximum Spread, computational speed, Hyper Volume, Inverted Generational Distance (IGD), and Generational Distance (GD). The results indicate that MOTTA exhibits superior performance,with 78.42% as thebest overallresult,and100% improvementin terms ofconvergence anddominationcompared tothe case study solutions(ER, ND, GD, and IGD). Overall, the findings have important implications for Hybrid flow shop scheduling in terms of the energy utilization model, reducing idle machine time, and the promising potential of MOTTA for application in other combinatorial scheduling challenges. This case study providessubstantial benefitsto the organization by effectively reducingits daily energy consumptionandequipment usage, while alsoenhancing resource management.